Pelatihan Penggunaan Media Online dalam Penjualan Parang dan Pisau Pada Pengrajin Besi Di Pulau Binongko - Samdin; Alida Palilati; Sudirman; Laxmi; Akifah; Rizky Nur Amalia; Wa Mirna; Muh. Reynaldi Ismail (Indo Publishing, 2025)
This community service program aims to enhance the digital marketing capabilities of blacksmith artisans in Binongko Island, a region known for its traditional craftsmanship of parang and knives. Limited market access and reliance on conventional sales methods have hindered the optimization of their economic potential. Through structured training, participants were introduced to various online media platforms, including Facebook, Instagram, and TikTok, to promote and sell their products more effectively. The training emphasized practical skills such as basic product photography, content creation, caption writing, audience engagement, and marketplace utilization. Hands-on sessions enabled artisans to upload product photos, create promotional videos, and interact with potential buyers. The results indicate a significant improvement in digital literacy, confidence, and motivation among participants to apply online marketing strategies. This program is expected to broaden market reach, increase product sales, and strengthen the cultural branding of Binongko’s traditional blacksmithing through digital platforms.